2020
DOI: 10.1016/j.ijnss.2020.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Care Dependency Scale in stroke survivors in Indonesian hospitals

Abstract: Purpose This study aimed to evaluate the psychometric properties of the Indonesian version of the Care Dependency Scale (CDS) among stroke survivors. Methods The study was undertaken in four hospitals. We analysed datasets obtained from 109 stroke survivors on inpatient wards and in outpatient clinics, who were rated by nurses to determine the CDS reliability coefficients. The Cronbach’s α and Cohen’s kappa coefficients were applied. Concurrent validity was conducted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…ADL performance was measured using the Indonesian version of the 10-item Barthel Index (BI), originally developed by Shah et al (1989), which is widely used in research and hospital settings (Nursiswati et al, 2020). A BI score of 10 indicates that the poststroke patient is “fully independent,” with 0 indicating “entirely dependent.” The maximum BI score is 100, with higher scores indicating a higher level of functional independence.…”
Section: Methodsmentioning
confidence: 99%
“…ADL performance was measured using the Indonesian version of the 10-item Barthel Index (BI), originally developed by Shah et al (1989), which is widely used in research and hospital settings (Nursiswati et al, 2020). A BI score of 10 indicates that the poststroke patient is “fully independent,” with 0 indicating “entirely dependent.” The maximum BI score is 100, with higher scores indicating a higher level of functional independence.…”
Section: Methodsmentioning
confidence: 99%
“…The BI measures physical functioning through 10 ADLs, while the CDS applies Henderson's theory of human needs. Various studies assessing the Indonesian CDS have confirmed its reliability and validity, establishing it as a dependable tool for measuring care dependency (Nursiswati et al, 2020). Scoring differs between the BI and CDS, with the BI using either a 5 or 10-point scale, while the CDS is more detailed, utilizing a 5-point scale.…”
Section: Discussionmentioning
confidence: 99%
“…The scale has also been adapted to Polish conditions [ 5 , 6 , 7 , 8 ]. The scale was developed following Virginia Henderson’s theory of nursing and includes both physical and psychosocial aspects, which are used to assess care dependency [ 9 , 10 , 11 ]. The results of earlier studies with the application of the CDS conducted in the Netherlands confirmed the utility of this tool in identifying whether patients are at risk of developing pressure ulcers or not, both in home and institutional care environments [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The connection between care dependency and other concomitant diseases such as dyspnea or incontinence was confirmed in a study carried out in Spain on a group of older patients suffering from heart failure [ 13 ]. The utility of the CDS was also demonstrated in Asia among stroke survivors receiving emergency or long-term treatment [ 11 ], as well as in Poland among geriatric ward patients suffering from exacerbation of chronic diseases or the incidence of new health problems [ 8 ] and among patients with mental disorders receiving psychogeriatric treatment within hospitals or outpatient care settings [ 5 ]. An age-related increase in care dependency among hospitalized patients was confirmed by means of the CDS in a study conducted in Germany [ 8 ].…”
Section: Introductionmentioning
confidence: 99%